Preparation and Characterization of Butterfly Pea (Clitoria ternatea L.) Nanoemulgel - Sapiun, Zulfiayu; Wicita, Prisca Safriani; Buloto, Ananda Sefriyani; Kamba, Vyani; Imran, Arlan K.; Buana, Whylies Agung Ajie; Hartati, Hartati; Banne, Yos (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Butterfly Pea or Asian pigeonwing (Clitoria ternatea L.) has been widely used by people. This flower species contains flavonoid and phenolic with antioxidant activities. Further, the antioxidant in flowers can be processed into nanoemulgel facial makeup. The emulgel is expected to provide better drug delivery, thus maximizing the anti-aging effects. AIM: The aim of this study was to identify the effect of the gel basis variation in the preparation and characterization of the nanoemulgel of Asian pigeonwing extract using the particle size analysis or PSA method. METHODS: In this experimental laboratory research, the independent variable comprised the variants of gelling agent bases, namely, carbopol 940, hydroxy prophyl methyl cellulose, and sodium carboxy methyl cellulose. Research tools involved magnetic stirrer, atomizer, spectrophotometer ultraviolet–visible, and particle size analyzer. The dependent variable consisted of the particle size, polydispersity index, and physical stability of nanoemulgel preparations. Instruments of the research encompassed three formula of emulgel, namely, F1 (using carbopol 940 0.2% base), F2 (using HPMC 0.2% base), and F3 (using Na CMC 0.2% base). All data were analyzed using the one-way ANOVA and Kruskal–Wallis test. The research was conducted from January to May 2021 at the Laboratory of Pharmacy Technology, Gorontalo Polytechnic of Health, the Natural Medicine Laboratory of the National Food and Drug Control Agency, and UII Laboratory Yogyakarta. RESULTS: The present work revealed that the F3 formula with Na CMC base is the best and most stable formula with the particle size measuring at 14.7 nm and polydispersity index (PDI) at 0.271. CONCLUSION: The gel base variation of the preparation produces different physical quality of Asian pigeonwing nanoemulgel with the best characteristics in the formula based on Na CMC.